Exploring Students' Critical Thinking Skills Through Expressive Responses: Science And Religion Integration Training - Hanafi, Yusuf; Saefi, Muhammad; Diyana, Tsania Nur; Ikhsan, M. Alifudin; Anam, Faris Khoirul; Ramadhan, Mochammad Rizal (Universitas Islam Lamongan, 2025)
Questions about the origins of humanity are challenging and motivating inquiries that can serve as a tool to encourage students to think critically. That context can also be provided to students when discussing the integration of science and religion. In this study, we measured the effectiveness of science and religion integration training specifically for Muslim students. This training intervention consists of three seminars, namely the integration of science and Islam methods, the context of human origins, and its writing, each developed by a mixed team of science and religion experts. By combining training observations and reflective essays, this study evaluates the training approach and how the program influences students' opinions/beliefs about the compatibility of science and religion. Specifically, this study explores students' ability to engage in critical thinking and express themselves when faced with explanations of science and religion simultaneously. As a result, there was a change in the beliefs of the students before and after the training, where the students shifted their opinions towards a more reconciliatory stance. However, the presence of a small number of students who are moving in opposite directions encourages educators to explore various methodologies for integrating science and religion that are more appropriate. Overall, this research contributes to the fundamental understanding of how students interpret science and religion, as well as the pedagogical approaches that can be used to navigate their interpretations from conflict to integration.